PENERAPAN SUMBER IDE TARI GANDRUNG BANYUWANGI PADA PEMBUATAN BUSANA EVENING - Umi Nur Habibah; Mrs Jumariah (Jurnal Socia Akademika, 2021)
The purpose of this research is: (1) pouring the source of banyuwangi gandrung dance ideas in creating evening fashion; and (2) knowing the panelist's response to evening fashion made in terms of fashion design, motif compatibility, and color compatibility. This study used quantitative descriptive methods to describe the process of making evening fashion with the source of gandrung dance ideas. Data collection uses questionnaires to find out the panelists' response to the results of evening fashion is reviewed in terms of fashion design, color compatibility, motif compatibility, and user documentation for the final results of evening fashion produced—quantitative analysis of data. The research results are in the form of a process to form into evening fashion with the source of the idea of Gandrung Banyuwangi dance. As many as 60% of panelists say the evening fashion design is good, and 40% say less good. Regarding the compatibility of motives, 95% of panelists stated compatibility, and 5% expressed mismatch. I was judging from the compatibility of color; as many as 95% stated compatibility and 5% stated less compatibility. So it can be said that evening fashion with the source of gandrung dance ideas using Banyuwangi batik cloth combined with lyrical udan striated, with Prada decorations, embroidery applications, and sequins have a good, elegant, and attractive form.